STEAM-Inquiry Learning Module Assisted by Liveworksheet for Multiplication Material in Elementary School - Ni'mah, Lina Nihayatun; Rusnilawati, Rusnilawati (Universitas Muhammadiyah Surakarta, 2023)
Mathematics often poses a daunting challenge for elementary school students, affecting their academic performance. Addressing this issue requires creating more engaging and innovative learning approaches. This research and development endeavour aim to assess the validity and practicality of a STEAM-based inquiry learning module assisted by a liveworksheet for multiplication material in third-grade elementary school. The study employed the Research and Development (R&D) method using the ADDIE model. The research involved 11 third-grade students at Tulip Putih Elementary School, and both quantitative descriptive analysis and qualitative description techniques were applied for data analysis. The validation results affirmed the suitability of the developed module, categorizing it as excellent. Trial results further demonstrated the practicality of the developed tool. Based on data analysis, it can be concluded that the STEAM-Inquiry Learning module assisted by a liveworksheet, developed for third-grade elementary school students studying multiplication, is suitable for implementation. The incorporation of technology within teaching modules enables educators to create interactive learning experiences. This can enhance the understanding of the material and subsequently influence the improvement of learning outcomes. The deployment of this instructional module stimulates students to be more engaged and active in class, nurturing critical, creative, confident, and analytical thinking skills